Can the Ames test provide an insight into nano-object mutagenicity? Investigating the interaction between nano-objects and bacteria. Issue 8 (December 2012) - Clift, Martin J. D.; Raemy, David O.; Endes, Carola; Ali, Zulqurnain; Lehmann, Andrea D.; Brandenberger, Christina; Petri-Fink, Alke; Wick, Peter; Parak, Wolfgang J.; Gehr, Peter; Schins, Roel P. F.; Rothen-Rutishauser, Barbara
Abstract The aim of this study was to assess the interaction of a series of well characterised nano-objects with the Gram negative bacterium Salmonella typhimurium, and how such an interaction may relate to the potential mutagenicity of nano-objects. Transmission electron microscopy showed that nano-objects (Au-PMA-ATTO NPs, CeO2 NPs, SWCNTs and MWCNTs), as well as CAFs entered S. typhimurium. Only DEPs did not penetrate/enter the bacteria, however, were the only particle stimulus to induce any significant mutagenicity through the Ames test. Comparison with a sophisticated 3D in vitro cell model showed CAFs, DEPs, SWCNTs and MWCNTs to cause a significant increase in mammalian cell proliferation, whilst both the Au-PMA-ATTO NPs and CeO2 NPs had not significant adverse effects. In conclusion, these results indicate that various of different nano-objects are able to penetrate the double-lipid bilayer of Gram negative bacteria, although the Ames test may not be a good indicator for nano-object mutagenicity.